Dermal mitoses correlate with surgical burden in lentigo maligna melanoma: PRAME for margin assessment - Leibing, Thomas; Ziemann, Clara; Géraud, Cyrill; Utikal, Jochen; Wohlfeil, Sebastian A. (Cancers, 2025)
Background/Introduction: Margin assessment in Lentigo maligna (LM) and Lentigo maligna melanoma (LMM) is challenging. Many of these lesions require extensive surgical procedures for R0 resections with unclear histological and clinical features predicting lateral spread. Recently, PRAME was described as a useful antibody to determine margins in these entities. However, several questions, like acceptable PRAME+ cell number and density in resection margins and optimal safety margins, especially in head and neck areas, remain. Methods: We analyzed cases of LMIS and LMM since the introduction of PRAME and before the introduction of PRAME, with more than 171 cases in total. We re-stained security margins with PRAME. Results: We identified a correlation between reported dermal mitoses in LMM and the number of surgical procedures. In many LMM cases before the widespread use of PRAME from our archives, we detected a high density of PRAME+ cells in melanoma security margins previously labeled tumor-free. No local recurrence could be identified in these cases, with the caveat of limited follow-up and small case numbers. Conclusions: Our findings raise important questions regarding margin assessment with PRAME and the reporting of residual cells in margins.